2006
DOI: 10.1177/0539018406069594
|View full text |Cite
|
Sign up to set email alerts
|

The subjective components of happiness and their attainment: a cross-cultural comparison between Italy and Cuba

Abstract: This study aims to identify the subjective components of happiness and to analyze their degree of attainment in two countries, Italy and Cuba, characterized by very different cultural and socio-economic structures. Two hundred and sixty-five subjects participated in a questionnaire study: 133 from Italy and 132 from Cuba. Respondents were asked to think of happiness and to write down at least 5 components that made them feel happy. A measure of overall happiness was also obtained by asking subjects to rate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 62 publications
5
29
0
1
Order By: Relevance
“…Importantly, this study also separately analyzed and reported data collected from a sample of 216 Italian citizens. Overall, the happiness definitions provided by these participants were semantically consistent with the happiness definitions obtained from the international sample previously examined by Delle Fave et al [28], and also with the happiness components found in the Italian studies by Galati, Sotgiu, and colleagues [2527]. Indeed, the life domains reported most frequently by these participants were, in order, interpersonal relationships , family , and health .…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Importantly, this study also separately analyzed and reported data collected from a sample of 216 Italian citizens. Overall, the happiness definitions provided by these participants were semantically consistent with the happiness definitions obtained from the international sample previously examined by Delle Fave et al [28], and also with the happiness components found in the Italian studies by Galati, Sotgiu, and colleagues [2527]. Indeed, the life domains reported most frequently by these participants were, in order, interpersonal relationships , family , and health .…”
Section: Introductionsupporting
confidence: 87%
“…In a series of subsequent questionnaire studies, Galati, Sotgiu, and colleagues [2527] investigated samples of citizens from the Italian and the Cuban population, including adults, older adults, as well as young students. Subjects who took part in these investigations were administered open-ended questions asking them to list the things that made them feel happy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Lyubomirsky's philosophy of well-being contrasts with the etymological meaning of the happiness concept: in fact, both the word eudaimonia in ancient Greek and the word felicitas in Latin originally referred to the concepts of 'good luck' and 'fate' (Minois, 2009). On the other hand, the theoretical framework proposed by Lyubomirsky is in accordance with what we know from empirical research on folk psychology of happiness (Galati, Manzano, & Sotgiu, 2006;Lu & Gilmour, 2004). Indeed, when asked to define what happiness is, people generally do not spontaneously mention themes and meaning components related to uncontrollable aspects of life such as luck or chance; this holds true for study participants living in both individualistic and collectivistic societies.…”
Section: Book Reviewsupporting
confidence: 55%
“…However, when comparing the US and Russian community samples, the results show a significant statistic for a baseline model, indicating a lack of comparability across samples. Galati et al (2006) identify the subjective components of happiness and analyze their degree of attainment in two countries, Italy and Cuba, characterized by very different cultural and socio-economic structures. Findings are discussed in relation to the socio-economic and cultural characteristics.…”
mentioning
confidence: 99%